1993
DOI: 10.2527/1993.714975x
|View full text |Cite
|
Sign up to set email alerts
|

Ovulatory and endocrine responses after active immunization of gilts against a synthetic fragment of bovine inhibin

Abstract: The objective of this study was to determine whether neutralizing endogenous inhibin would affect ovulation rate and serum concentrations of FSH, LH, estradiol-17 beta, and progesterone in gilts. At wk 0, during their second postpubertal estrous cycle, gilts (195 +/- 2.4 d of age) were given a primary immunization against the 1-26 gly-tyr NH-terminal amino acid sequence of bovine inhibin-alpha conjugated to human alpha globulin (INH; n = 10) or against human alpha globulin alone (control; n = 10). The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Fecundin ® vaccination has been reported to increase ovulation rate and litter size in sheep and cattle with optimal results with antibody titers between 1:500 and 1:3000 (Reeves et al 1989). In swine, two reports have indicated that inhibin vaccination increased ovulation rate although the required threshold titers differed [B 0 = 5-7% at 1:800 dilution Brown et al 1990; B 0 = 9-22% at 1:4000 serum dilution (King et al 1993)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecundin ® vaccination has been reported to increase ovulation rate and litter size in sheep and cattle with optimal results with antibody titers between 1:500 and 1:3000 (Reeves et al 1989). In swine, two reports have indicated that inhibin vaccination increased ovulation rate although the required threshold titers differed [B 0 = 5-7% at 1:800 dilution Brown et al 1990; B 0 = 9-22% at 1:4000 serum dilution (King et al 1993)].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to induce a 20% increase in lamb crop (Reeves et al 1989). Attempts to immunize against inhibin have increased the total number of lambs born (Wrathall et al 1992), increased twinning rate in cattle (Morris et al 1993) and increased ovulation rate in swine (Brown et al 1990;King et al 1993). To date, only one report has indicated that immunoneutralization of an endogenous hormone, somatostatin, can increase litter size in swine (Kirkwood et al 1990).…”
mentioning
confidence: 99%
“…In gilts, FSH administration induces follicular recruitment and increases the ovulation rate in a dose-dependent manner [32][33][34]. Active immunization against inhibin, which is produced by granulosa cells and inhibits FSH excretion, increased the number of ovulations [35,36]. The number of recruited follicles might depend on blood FSH levels and/or on the number of follicles responsive to FSH present at the time of recruitment.…”
Section: Follicular Developmentmentioning
confidence: 99%
“…Experiments with FSH receptor (FSHR) knockout mice and hypophysectomized rodents have shown that FSH is essential for formation of the antrum in secondary follicles and postantral follicular development in tertiary follicles [42]. Active immunization against inhibin increased the number of ovulations in sows [43,44], and injection of inhibin into the ovarian bursa of immature rats increased the number of mediumsized antral follicles [45], indicating that inhibin acts to prevent follicular development. Although atresia can occur at any time during follicular development, the majority of follicles become atretic during the early antral stage of development [40].…”
Section: Regulation Of Follicular Development and Atresiamentioning
confidence: 99%